Uji Proximate Tepung Jagung dari Limbah Tongkol Jagung Pulut secara Fermentasi - Mirnawati Mirnawati; Rizka Octavia (Politeknik Negeri Cilacap, 2021)
Waxy corn is widely developed in several areas in South Sulawesi. From year to year the productivity of pulut corn has increased, this also shows that agricultural waste production has also increased. The agricultural waste produced by corn is cobs. The purpose of this study was to determine the processing of pulut corn cobs into corn flour and to determine the characterization of the quality of corn flour, especially the proximate test based on SNI standards. The research method is the gravimetric method, the results of the corn flour test show that the proximate content (moisture content, ash content, and protein content) with successive values of 0.07%, 17.49%, 1.9 x 106 has met the standard standards. Indonesian National (SNI) (SNI 01-3751-2009), except for moisture content with a value of 14.32% which indicates that corn flour has a short shelf life. Waxy corn is widely developed in several areas in South Sulawesi. Pulut corn contains 100% amylopectin which provides a sweet, fluffier taste and good texture.